OPTIMALISASI DAN ANALISIS DESAIN PARAMETER SEISMIK 3D DARAT BERDASARKAN MODEL GEOLOGI LAPANGAN “RL” - Ravide Lubis; Bagus Sapto Mulyatno; Karyanto Karyanto (Engineering Faculty Universitas Lampung, 2018)
The design of 3D land seismic parameters is a preliminary step before the acquisition of 3D land seismic data to obtain seismic data quality and efficient survey budget. The objective of this research is to obtain high quality of 3D land seismic data based on fold coverage spread on each target layer. The method used is based on the principle of wave propagation or ray tracing method on each target layer, wherein each wave reflection point (bin) will have a different value of fold so that the required configuration of the stretch that will result in the optimal spread of the fold. The applied stretch configurations are orthogonal, brick, zig-zag and slanted where each stretch configuration uses two types of templates that is narrow and wide azimuth. From the simulation analysis results of several stretch configurations in the survey area, then the optimal stretch configuration will be obtained in the survey area. The stretch configuration will be applied is the configuration of orthogonal stretch with narrow azimuth type template. Consideration of the selection of this stretch configuration because it has a more evenly folding effect on the target layer than with other stretch configurations. Furthermore, to obtain the configuration of the appropriate stretch of field conditions, the source point is moved outside the obstacle zone so that the quality of seismic data is maintained.